"Your Professor Will Know You as a Person": Evaluating and Rethinking the Relational Boundaries Between Faculty and Students. (February 2017) - Chory, Rebecca M.; Offstein, Evan H.
Over the past 30 years, several management educators have urged faculty to reexamine their relationships with students. To do this, many have proposed novel metaphors to reconceptualize the faculty-to-student relationship. These include embracing students not as pupils to be taught but rather as clients, consumers, and even employees. At the heart of these metaphors, though, is a subtle and not-so-subtle pressure to build more intimate, personal, and close relationships with students. As more and more stories surface in the scholarly and practitioner press about "close relationships" that have devolved into sad and disappointing outcomes for students, faculty, and universities, it is necessary to revisit the core assumption that closer is better. In this essay, we describe the forces driving more personal relationships between faculty and students. Next, we question the assumptions along with the unintended consequences of adopting more intimate relationships with students. Finally, we conclude by challenging management educators to rethink the notion of professional calling along with the notion of pedagogical caring. To be sure, we offer some prescriptions and principles to help management educators navigate the student–faculty relationship—a relationship, we believe, more in flux now than in any other time in the history of higher education.